Modulation of Dendritic Cell Apoptosis and CD8+ Cytotoxicity by Histamine: Role of Protein Kinase C - Julieta Alcain; Enrique Podaza; María Soledad Gori; Gabriela Salamone; Mónica Vermeulen (Hindawi Limited, 2017)
Dendritic cells (DC) are able to present extracellular antigens associated with the molecules of the major histocompatibility complex class I. In a previous work, we demonstrated that the histamine (HIS), acting through H1/H4 receptors, increases the cross-presentation of soluble ovalbumin by murine DC and can enhance the recruitment of specific CD8+ T lymphocytes during the development of chronic inflammatory responses. Here, we studied in more depth the mechanisms underlying this enhancement. We showed that the cytotoxicity of specific CD8+ lymphocytes is increased in HIS-treated DC and it is lost by inhibition of vacuolar-ATPase that prevents endosome acidification. It is known that HIS acts through G protein-coupled receptors. The H1/H4 receptors are associated with a Gq subunit, which involves PKC signaling, a pathway related to the apoptotic process. Interestingly, we demonstrated for the first time that HIS prevents DC apoptosis induced by heat shock through the inhibition of caspase-3, a mechanism dependent on PKC activation, since it is reversed by its inhibition. By contrast, cytolytic activity of T lymphocytes induced by HIS-stimulated DC was independent of PKC pathway.